CENTRE FOR MARINELIFE CONSERVATION AND COMMUNITY DEVELOPMENT’S STRATEGY AS AN NGO IN STRENGTHENING THE SOCIALIST REPUBLIC OF VIETNAM’S COASTAL COMMUNITY RESILIENCE - Pertiwi, Diyah Ayu; Susiatiningsih, Hermini (Journal of International Relations, 2018)
Climate change is the biggest challenge for humanity in this century as it causesproblematic environmental changes and destructive weather conditions. Vietnamesecoastal community were considered as the most vulnerable people suffering from theimpacts of climate change as their livelihoods are depending on the marine-basedresources. However, this research found that the coastal people today are more able toadapt, adjust and overcome the negative impacts of climate change after receivingintervention from Centre for Marinelife Conservation and Community Development(MCD). This research aims to describe the coastal community condition and explain thestrategies used by MCD to strengthen the coastal community resilience in Vietnam. Thisqualitative research is developed using literary technique. In which, author collected datafrom secondary sources, comprise of publications from of MCD, other related ministriesand institutions. Using the conceptual frameworks of NGO Concept and TransnationalAdvocacy Network, this research answers the question that MCD uses its strategies bymaintaining cooperative manner to deliver its influence within the socialist governmentutilizing the Transnational Advocacy Network and conducting small-scale change andlarge-scale change. These strategies allow MCD to strengthen Vietnamese coastalcommunes’ resilience and to sustain under the socialist regime.